Understanding online shopping experiences with augmented reality (AR) mobile apps: A grounded theory approach - Wan Jusoh, Wan Amiera; Nor Irvoni Mohd Ishar, Nor Irvoni Mohd Ishar; Fikry@Aziz, Amily (Jurnal Evolusi, 2023)
Following In the post-pandemic landscape, the resurgence of in-store shopping has caused a decline in online purchases. However, the retail industry has witnessed a surge in the adoption of augmented reality (AR) technology as businesses seek innovative ways to revitalize the online shopping experience and maintain a competitive edge. This study delves into the realm of customer experience with augmented reality, specifically focusing on mobile apps tailored for cosmetic products. The research methodology employed in-depth interviews to gather qualitative data, allowing for a nuanced exploration of consumer perceptions and preferences. The analysis reveals three pivotal dimensions crucial for the success and acceptance of AR mobile apps among online shoppers: hedonic experience, utilitarian experience, and immersive experience. The hedonic experience emphasizes the emotional and sensory gratification derived from using AR apps, providing customers with an enjoyable and engaging shopping journey. Simultaneously, the utilitarian experience underscores the practical benefits and functionality that AR technology brings, enabling users to make informed decisions about cosmetic products. Lastly, the immersive experience immerses customers in a digitally enhanced shopping environment, blurring the lines between the virtual and physical realms. For retailers to harness the full potential of AR in the cosmetic retail sector, a strategic fusion of these three experiential dimensions is imperative. This study contributes valuable insights for businesses aiming to leverage AR technology effectively, ensuring a compelling and satisfying online shopping encounter for consumers in the ever-evolving retail landscape.